Retinal Microcirculation as a Correlate of a Systemic Capillary Impairment After Severe Acute Respiratory Syndrome Coronavirus 2 Infection - Hohberger, Bettina; Ganslmayer, Marion; Lucio, Marianna; Kruse, Friedrich; Hoffmanns, Jakob; Moritz, Michael; Rogge, Lennart; Heltmann, Felix; Szewczykowski, Charlotte; Fürst, Julia; Raftis, Maximilian; Bergua, Antonio; et al. (Frontiers in Medicine, 2021)
Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) causing Corona Virus Disease-2019 (COVID-19), affects the pulmonary systems via angiotensin-converting enzyme-2 (ACE-2) receptor being an entry to systemic infection. As COVID-19 disease features ACE-2 deficiency, a link to microcirculation is proposed. OCT-angiography (OCT-A) enables non-invasive analysis of retinal microvasculature. Thus, an impaired systemic microcirculation might be mapped on retinal capillary system. As recent OCT-A studies, analyzing microcirculation in two subdivided layers, yielded contrary results, an increased subdivision of retinal microvasculature might offer an even more fine analysis. The aim of the study was to investigate retinal microcirculation by OCT-A after COVID-19 infection in three subdivided layers (I). In addition, short-term retinal affections were monitored during COVID-19 disease (II). Considering (I), a prospective study (33 patientspost-COVID, 28 controls) was done. Macula and peripapillary vessel density (VD) were scanned with the Spectralis II. Macula VD was measured in three layers: superficial vascular plexus (SVP), intermediate capillary plexus (ICP), and deep capillary plexus (DCP). Analysis was done by the EA-Tool, including an Anatomical Positioning System and an analysis of peripapillary VD by implementing BMO landmarks. Overall, circular (c1, c2, c3) and sectorial VD (s1-s12) were analyzed. Considering (II), a retrospective study of 29 patients with severe complications of COVID-19 infection, hospitalized at the intensive care unit were monitored for retinal findings at bedside during hospitalization. (I) Overall (p=0.0133) and circular (c1, p=0.00257; c2, p=0.0067; c3, p=0.0345) VD of ICP were significantly reduced between patientspost-COVID and controls, respectively. Overall (p=0.0179) and circular (c1, p=0.0189) peripapillary VD were significantly reduced between both groups. Subgroup analysis of hospitalized vs. non- hospitalized patientspost-COVID yielded a significantly reduced VD of adjacent layers (DCP, SVP) with increased severity of COVID-19 disease. Clinical severity parameters showed a negative correlation with VD (ICP) and peripapillary VD. (II) Funduscopy yielded retinal hemorrhages and cotton wool spots in 17% of patients during SARS-CoV-2 infection. As VD of ICP and peripapillary region were significantly reduced after COVID-19 disease and showed a link to clinical severity markers, we assume that the severity of capillary impairment after COVID-19 infection is mapped on retinal microcirculation, visualized by non-invasive OCT-A.